ECONOMIC EFFICIENCY TO USE OF INPUT (SUBSIDIZED FERTILIZER) IN RICE FARMING IN MUSI RAWAS REGENCY (Case Study of Sentra Beras Sub-district) - Primalasari, Ira; Octalia, Vera (Journal of Agri Socio Economics and Business, 2024)
This research aims to find out how the use of inputs affects the results of lowland rice production and analyze the economic efficiency of using subsidized fertilizers. This research was conducted in three sub-districts which are rice centers in Musi Rawas Regency, namely Purwodadi, Tugu Mulyo and Muara Beliti sub-districts. The research sample was 150 farmers spread across the three sub-districts. Data collection used primary and secondary data. Data analysis used multiple linear regression and Marginal Product Value. The research results show that the factors that influence rice production results are labor and urea fertilizer, while seed factors, phonska fertilizer, and pesticides do not affect rice production. The results of calculating the economic efficiency of subsidized fertilizer, namely urea fertilizer, have the value that the efficiency index value NPMx/Px > 1, namely 8.10. This means that the use of subsidized urea fertilizer is not efficient, and Phonska fertilizer has an efficiency index value of NPMx/Px > 1, namely 3.22. This means that the use of subsidized Phonska fertilizer is not yet efficient.